Role of progenitor cell producing normal vagina by metaplasia in laparoscopic peritoneal vaginoplasty - Pravin N Mhatre (Journal of Human Reproductive Sciences, 2016)
Context: Host of vaginoplasty techniques have been described. None has been successful in developing normal vagina. Laparoscopic peritoneal vaginoplasty (LPV) is performed in Mayer-Rokitansky-Küster-Hauser syndrome (MRKHS) culminating in normal vagina. Aims: This study aims to confirm normal development of neovagina by anatomical and functional parameters of histology, cytology, and ultrasonography (USG) in LPV. To identify peritoneal progenitor cell by OCT4/SOX2 markers. To demonstrate the metaplastic conversion of peritoneum to neovagina and the progenitor cell concentration, distribution pattern. Settings and Design: This is prospective experimental study, conducted at teaching hospital and private hospital. Subjects and Methods: Fifteen women of MRKHS underwent LPV followed by histology, cytology, two-/three-dimensional USG of neovagina. Four women underwent peritoneal biopsy for identification of progenitor cells with OCT4/SOX2 markers. One patient underwent serial biopsies for 4 weeks for histology and progenitor cell immunohistochemistry. Results: Normal vaginal histology and cytology were apparent. USG of neovagina showed normal appearance and blood flow. Two peritoneal samples confirmed the presence of progenitor cells. Serial biopsies demonstrated the epithelial change from single to multilayer with stromal compaction and neoangiogenesis. The progenitor cells concentration and different distribution patterns were described using SOX2/OCT4 markers. Conclusions: We have shown successful peritoneal metaplastic conversion to normal vagina in LPV. The progenitor cell was identified in normal peritoneum using SOX2/OCT4 markers. The progenitor cell concentration and pattern were demonstrated at various stages of neovaginal development.